Osthole: An up-to-date review of its anticancer potential and mechanisms of action - Yang, Shaojie; Dai, Wanlin; Wang, Jingnan; Zhang, Xiaolin; Zheng, Yuting; Bi, Shiyuan; Pang, Liwei; Ren, Tengqi; Yang, Ye; Sun, Yang; Zheng, Zhuyuan; Wu, Shuodong; et al. (Frontiers in Pharmacology, 2022)
With its high incidence and mortality rates, cancer is one of the largest health problems worldwide. Investigating various cancer treatment options has been in the focus of domestic and foreign researchers, and significant progress has been made in the study of the anticancer effects of traditional Chinese medicines. Osthole, a coumarin compound extracted from Cnidium monnieri (L.) Cuss., has become a new research hotspot. There have been many reports on its anticancer effect, and recent studies have elucidated that the underlying mechanism of action mainly involves inhibiting cancer cell proliferation, inducing cancer cell apoptosis, inhibiting invasion and migration of cancer cells, inhibiting cancer angiogenesis, increasing sensitivity to chemotherapy drugs, and reversing multidrug resistance of cancer cells. This mini-review summarizes the research progress on the anticancer effect of osthole in recent years.